Interleukin-18 in chronic pain: Focus on pathogenic mechanisms and potential therapeutic targets - Jie Ju; Zheng Li; Xiaoqian Jia; Xiaoling Peng; Jihong Wang; Feng Gao (Elsevier, 2024)
Chronic pain has been proven to be an independent disease, other than an accompanying symptom of certain diseases. Interleukin-18 (IL-18), a pro-inflammatory cytokine with pleiotropic biological effects, participates in immune modulation, inflammatory response, tumor growth, as well as the process of chronic pain. Compelling evidence suggests that IL-18 is upregulated in the occurrence of chronic pain. Antagonism or inhibition of IL-18 expression can alleviate the occurrence and development of chronic pain. And IL-18 is located in microglia, while IL-18R is mostly located in astrocytes in the spinal cord. This indicates that the interaction between microglia and astrocytes mediated by the IL-18/IL-18R axis is involved in the occurrence of chronic pain. In this review, we described the role and mechanism of IL-18 in different types of chronic pain. This review provides strong evidence that IL-18 is a potential therapeutic target in pain management.